Test–retest reliability of RC21X: a web-based cognitive and neuromotor performance measurement tool. (10th August 2020) - Saganis, Xanthia; Goreczny, Anthony J; Kondraske, George; Berman, Masha; Comnick, Ian; Allen, Tyler; Nussbaum, Paul D
Abstract: Objective: As computerized cognitive testing becomes increasingly popular in clinical and research settings, conducting studies on efficacy and psychometric properties is essential. One such program is RC21X, a web-based brain performance measurement tool. Based on empirically supported neurocognitive and neuromotor tasks, the 12-min test consists of 15 modules measuring memory, motor coordination, processing speed, and executive functioning. Because individuals may use RC21X repeatedly to track changes in cognitive performance, establishing reliability of the program is imperative. The current study examined test–retest reliability of RC21X within a 2-week period. Method: The sample consisted of 222 individuals: 192 (86.5%) were male, and 30 (13.5%) were female. Average age was 44.06 years ( SD = 17.76), with ages ranging from 7 to 82 years. We computed Pearson's correlation coefficients for module and composite scores to determine reliability between performance at times 1 and 2. Results: All correlations were statistically significant ( p < .001). The 2-week test–retest reliability for composite score was 0.72, with subtest coefficients ranging from 0.54 on an auditory memory recognition task to 0.89 on a finger tapping task. We replicated these analyses with participants' ( n = 43) test sessions 3 and 4; we found similar results to those from test 1 and test 2 analyses, suggesting stability of results over multiple administrations. Conclusions: Results for RC21X were comparable to existing literature that supports moderate to high reliability of other computer-based tests. Although future research needs to investigate validity of RC21X, our findings support potential applications in research, clinical use, and personal brain performance measurement.